Análisis y fomento de las competencias clave del educador deportivo que trabaja con adolescentes en riesgo de exclusión social a través del ocio = Analysis of the Socio-educational Competences of the Sports Educator who Works with Children and Adolescents at Risk through Leisure - Galán-Casado, Diego (Cauriensia, 2024)
Sports leisure is one of the most important and representative types of leisure in today's society for working with children and adolescents at risk of social exclusion. This article aims to analyze the self-perception of the competencies of the sports educator from a socio-educational program that aims to improve training and professional practice. A sample of 78 individuals was used by means of a non-probabilistic convenience sampling, all of them belonging to different entities and who develop their role in psychoeducational intervention through sport. The Caratteristiche del professionista dello sport test was used and was applied before and after the training received. The results obtained reflect statistically significant differences in 12 of the 31 paired variables, as well as in the total score, evidencing the effectiveness of the program in improving the competencies of these professionals when working with children and adolescents at risk of social exclusion through sport.